Advocating for Justice: The Role of Amnesty International Indonesia in the Haris and Fatia Case - Nazwa Nafisha Januariska; Shakila Adzira Putri Prasetyo; Muradi (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
This study examines the role of Amnesty International Indonesia in the criminalization case against Haris Azhar and Fatia Maulidiyanti, who criticized the involvement of public officials in Papua’s mining industry. The case illustrates serious challenges to freedom of expression in Indonesia, particularly through the use of elastic articles in the Electronic Information and Transactions Law (UU ITE). The purpose of this research is to analyze how Amnesty International Indonesia performs its role as a civil society organization in strengthening democracy and protecting human rights. This study employs a descriptive-qualitative method with a literature review, drawing on official documents, human rights reports, media coverage, and relevant academic studies. The findings indicate that Amnesty International Indonesia plays a strategic role through three main civil society functions: advocacy, empowerment, and social control. The organization actively issued public statements, conducted campaigns, mobilized solidarity actions, and sent formal communications to both the government and international institutions. In addition, Amnesty raised public awareness of the risks of criminalization and monitored the judicial process, which was often deemed unjust. Thus, Amnesty International Indonesia is proven to be an important actor in expanding democratic space and defending freedom of expression in Indonesia.